Effects of Non Tariff Barriers on Maize Trade in Mbozi and Momba Districts of Tanzania - Petro, Maziku (International Journal of Economics, Business and Management Studies, 2016)
This paper examined the effects of NTBs on maize price received by smallholder famers and traders in Mbozi and Momba districts of Mbeya region in Tanzania. Cross sectional data were collected from 240 smallholder farmers and 50 traders from selected villages and markets using structure questionnaires and Focused Group Discussion. A two stage - stratified sampling procedures were used in the selection of farmers. Findings from study show that, NTBs has an inversely relationship with maize prices having coefficient valued at -0.062. This implies that, for a unit increase in NTBs costs there would be a 6.2% decline in farmer’s prices in the rural areas and rise in consumer’ prices by the same percent in the urban centers. Moreover, maize prices seem to decrease with an increase in distance from the rural markets to urban markets and that contributions of NTBs on producer prices were higher between rural and districts markets. The paper concluded that, NTBs play a significant contribution on the increase in transaction costs which leads to lowering farm gate prices in the rural and increased consumer prices in the urban areas. It is therefore recommended that, protective food policy such as NTBs strategies should be minimized in order to maintain reasonably high prices in rural areas and low prices in urban areas.